2020
DOI: 10.3390/met10081010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strengthening in S235JR Steel Sheets through Vibration-Assisted Ball Burnishing

Abstract: The superficial effect of hardening caused after vibration-assisted ball burnishing and its consequences in the tensile behavior of a carbon steel material are studied in this paper. As ball burnishing affects the material to hundredths of micrometers in depth through plastic deformation, the overall macro effect of this modification was studied. Different levels of preload and vibration amplitude were studied to address the described issue. The study was done in two phases. First of all, the depth to which ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…The process does not remove any material. The method causes the plastic deformations on the part surface which creates residual stresses in the worked surface and improve surface quality [7]. Priyadarsini et al, recently showed an overview of past research on surface integrity in burnishing processes; ball burnishing, roller burnishing and low plasticity burnishing (LPB) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The process does not remove any material. The method causes the plastic deformations on the part surface which creates residual stresses in the worked surface and improve surface quality [7]. Priyadarsini et al, recently showed an overview of past research on surface integrity in burnishing processes; ball burnishing, roller burnishing and low plasticity burnishing (LPB) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in sheet metal forming operations where the material is deformed by the action of rigid tools, the friction between the sheet and tools, affecting the strain distribution of the sheet, takes a special role on the fracture of the material [4][5][6][7][8][9]. Therefore, several authors have focused on the usage of surface plastic deformation techniques, such as the burnishing process, to improve material characteristics like roughness, hardness, fatigue life, microstructure, corrosion resistance and the mechanical properties of materials [10][11][12][13][14]. In recent years, burnishing is considered as one of the outstanding cold-forming finishing processes employed as a surface treatment technique for the manufacturing industry [15].…”
Section: Introductionmentioning
confidence: 99%
“…Burnishing force is most often generated with the spring [6][7][8][9][10][11][12][13][14][15], pressurized fluid [16,17], and high stiffness tools [18][19][20]. There are also hybrid ball burnishing tools, such as vibrationassisted ball burnishing tools [21][22][23][24][25][26][27][28][29][30][31][32], magnetic-assisted ball burnishing tools [33,34], etc. Burnishing force is usually generated by a single ball, although ball burnishing tools with multiple balls also exist.…”
Section: Introductionmentioning
confidence: 99%